Identification of molecular pathways associated with Newcastle disease virus (AF2240) persistent infection in urothelial cell carcinoma - Ahmad, Umar (2020)
Urothelial cell carcinoma (UCC) poor prognosis is due to limited treatment options for advance disease and resistance to conventional therapies. Newcastle disease virus (NDV) is a promising novel therapeutic avenue, killing tumour cells while sparing normal cells. However, wild-type NDV AF2240 has been found to persistently infect a subpopulation of cancer cells in vitro, making these cells less susceptible to NDVmediated oncolysis. Moreover, the exact molecular mechanism by which UCC cells acquire NDV persistent infection has not been elucidated. Therefore, the aim of this study was to stratify UCC cell lines based on their sensitivity toward NDV-mediated oncolysis and perform transcriptome profiling to identify potential molecular pathways associated with NDV persistent infection in UCC. NDV-mediated oncolysis on bladder cancer cell lines was assessed by infecting the cells with NDV at MOI of 1 and percentage cell viability was determined using WST-1 assay. Persistent infection was developed in TCCSUP cells by infecting the cells with NDV at low MOI. Confirmation of NDV persistent infection was carried out using ELISA, conventional PCR, flow cytometry, RT-qPCR and transmission electron microscope (TEM). While validation of RNA-Seq data was conducted using RT-qPCR. After quality control analysis, in silico quantification of differentially expressed transcripts (DEGs) and functional annotation analysis were carried out using the DESeq2 package in R and metascape respectively. Hallmark pathways enrichment analysis was performed using fast gene enrichment analysis (FGSEA) package in R and Molecular Signature Database (MSigDB). Prediction of related genes was manually curated in MS word excel and the resulting similarity genes were used to mine the GeneCards database for their function. PPI network was performed using NetworkAnalyst via STRING Interactome, while module analysis was carried out by Cytoscape. Then, nodes that are functionally connected in the PPI network were visualized using path explorer function and the top candidate hub genes were further validated using Oncomine database. Amongst the cell lines tested, UMU16, RT112, UMUC10, HT1376, EJ28, UMUC3, TCCSUP and SCaBER were less sensitive to NDV infection. Cytopathic effect (CPE) was observed with progressive acute lysis crisis when TCCSUP cells were infected with NDV at low MOI. Cells that survived the viral infection after 5 days were termed as persistently infected TCCSUPPi cells. PCR and qPCR analysis confirmed the presence of viral genes in these cells. Flow cytometric analysis demonstrated that ~85% and ~90% of TCCSUPPi and EJ28Pi cells maintained GFP expression even after fifteen passages when infected with recombinant NDV (rNDV-GFP). NDV particles were observed in some endosomes of the persistent TCCSUPPi cells and striking ultrastructural changes were found in both the persistent TCCSUPPi and EJ28Pi cells. Furthermore, both TCCSUPPi and EJ28Pi cells developed an antiviral state by producing low levels of interferon (IFN) beta. Transcriptomic profiling identified 63 and 134 differentially expressed transcripts in persistently infected TCCSUPPi and EJ28Pi cells, respectively. Of 63 transcripts in TCCSUPPi cells, 25 genes were upregulated (log2 fold-change ≤ 0) and 38 genes were downregulated (log2 fold-change ≥ 0). These genes were significantly enriched in molecular function of calcium binding (GO:0005509) and DNA-binding transcription repressor activity, RNA polymerase II-specific (GO:0001227) and the enriched important upregulated pathways were mainly heme metabolism, TGF-beta signaling and spermatogenesis. Whilst in EJ28Pi, 55 genes were upregulated (log2 fold-change ≤ 0) and 79 genes were downregulated (log2 fold-change ≥ 0). These transcripts resulted in significantly enriched molecular functions such as protein domain specific binding (GO:0019904) and RNA polymerase II regulatory region sequence-specific DNA binding (GO:0000977). The important enriched dysregulated pathways include allograft rejection, KRAS signaling up, interferon gamma response, angiogenesis, apoptosis, and xenobiotic metabolism. Based on PPI network analysis, the bridges were found mainly from pathways of p53 signaling, ECM-receptor interaction, and TGF-beta signaling by the upregulated mRNAs, to the antigen processing and presentation, protein processing in endoplasmic reticulum, complement and coagulation cascades by the downregulated mRNAs in NDV persistent TCCSUPPi cells. Comparatively, in persistently infected EJ28Pi cells, connections were identified mainly from pathways of renal carcinoma, viral carcinogenesis, Ras signalling and cell cycle by the upregulated mRNAs, to the Wnt signalling, HTLV-I infection and pathways in cancer by the downregulated mRNAs. This connection was mainly dependent on of RPL8- HSPA1A/HSPA4 in TCCSUPPi cells and EP300, PTPN11, RAC1 - TP53, SP1, CCND1 and XPO1 in EJ28Pi cells. Oncomine validation showed that the top hub genes identified in the network that includes RPL8, THBS1, F2 from TCCSUPPi and TP53 and RAC1 from EJ28Pi are involved in development and progression of bladder cancer. Protein-drug interaction network analysis identified several potential drug targets that could potentially prevent UCC cells from acquiring NDV persistent infection. In summary, this study presents the successful development of NDV persistent infection in bladder cancer cells in vitro. The global transcriptomic (RNA-Seq) profiles provide an insight to how UCC cells acquire NDV persistent infection. Resolving the precise mechanism of persistent infection will facilitate the use of NDV for treatment of UCC in the clinic.